High-Throughput DNA Plasmid Transfection Using Acoustic Droplet Ejection Technology. (April 2019) - Colin, Béatrice; Deprez, Benoit; Couturier, Cyril
The Labcyte Echo acoustic liquid handler allows accurate droplet ejection at high speed from a source well plate to a destination plate. It has already been used in various miniaturized biological assays, such as quantitative PCR (q-PCR), quantitative real-time PCR (q-RT-PCR), protein crystallization, drug screening, cell dispensing, and siRNA transfection. However, no plasmid DNA transfection assay has been published so far using this dispensing technology. In this study, we evaluated the ability of the Echo 550 device to perform plasmid DNA transfection in 384-well plates. Due to the high throughput of this device, we simultaneously optimized the three main parameters of a transfection process: dilution of the transfection reagent, DNA amount, and starting DNA concentration. We defined a four-step protocol whose optimal settings allowed us to transfect HeLa cells with up to 90% efficiency and reach a co-expression of nearly 100% within transfected cells in co-transfection experiments. This fast, reliable, and automated protocol opens new ways to easily and rapidly identify optimal transfection settings for a given cell type. Furthermore, it permits easy software-based transfection control and multiplexing of plasmids distributed on wells of a source plate. This new development could lead to new array applications, such as human ORFeome protein expression or CRISPR-Cas9-based gene function validation in nonpooled screening strategies.